Pengaruh Pemberian Asap Cair Galam pada Edibel Film Terhadap Kemunduran Mutu Ikan Patin (Pangasius sp.) [The effect of galam liquid smoke (Malaleuca leucadendra) incorporated with edible film as preservative for catfish (Pangasius sp.) during storage] - Salim, Rais; Khairiah, Nadra; Rahmi, Nazarni (Jurnal Riset Industri Hasil Hutan, 2020)
Galam liquid smoke isa liquid product derived from carbonization process of Galam wood (Malaleuca leucadendra) whichcan be used as natural preservative to fish. The incorporated edible film packaging with liquid galam wood is a good alternative to inhibit the deterioration of fish quality during storage. This study aims to determine the effect of liquid smoke of galam wood incorporated intoediblefilm to the deterioration of catfish(Pangasius sp)quality. The treatment factors used were (i) the edible film-gelatineformulation (G), gelatine-pectin (G-P), liquidsmoke-gelatine(G-AC) and gelatine-pectin-liquidsmoke(G-P-AC). It was compared with control (without treatment). The other factors were (ii) storage duration of 0 hour, 2 hours, 4 hours and 6 hours. The observed degradation parameters were Total Volatile Base-Nitrogen (TVBN) and microbiological testing. After being stored for6 hours, the highest value of TVBN was found in the control without treatment (54 mgN/100g),while the lowest TVBN value was gelatine-pectine-liquid smoke (18mgN/100g). The microbiological testshowed thatthe highest TP value wasfound in the control which reached 1.6x10^9, while the gelatine, gelatine-pectin, gelatine-liquid smoke and gelatine-pectin-liquid smoke were log 5.7x10^8; 1.0x10^8; 3.5x10^8; and 7.0x10^8respectively. The gelatine-pectin-liquid smoke (G-P-AC) treatment is able to inhibit the decrease of catfish quality on TVBN value at 6 hours of storage, while TPC value is more stable on gelatine-smoke treatment (G-AC) at 2 to 6 hours. The results of this study indicate that the addition of liquid smoke is able to inhibit the declining quality of catfish.